An abscopal effect in a case of concomitant treatment of locally and peritoneally recurrent gastric cancer using adoptive T‐cell immunotherapy and radiotherapy. Issue 4 (15th February 2017) - Sato, Hiro; Suzuki, Yoshiyuki; Yoshimoto, Yuya; Noda, Shin‐ei; Murata, Kazutoshi; Takakusagi, Yosuke; Okazaki, Atsushi; Sekihara, Tetsuo; Nakano, Takashi
Key Clinical Message: The mechanism of abscopal effect is becoming clear by the progress of cancer immunology. A 54‐year‐old male with recurrent gastric cancer presented an abscopal effect after radiotherapy with concurrent adoptive T‐cell immunotherapy (immunoradiotherapy). Immunoradiotherapy has potential to induce abscopal effect by strengthening systemic antitumor immunity even in recurrent cancer. Abstract : The mechanism of abscopal effect is becoming clear by the progress of cancer immunology. A 54‐year‐old male with recurrent gastric cancer presented an abscopal effect after radiotherapy with concurrent adoptive T‐cell immunotherapy (immunoradiotherapy). Immunoradiotherapy has potential to induce abscopal effect by strengthening systemic antitumor immunity even in recurrent cancer.